Application of The Welch – Powell Algorithm on Graph Coloring in Mapping Village Area in Alor Island, East Nusa Tenggara - Landerius Maro (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to introduce the concept of graph coloring using the Welch – Powell algorithm in an effort to help related parties, in this case the government in the Alor Island region, to facilitate the coloring of village maps. The method used in this research is descriptive quantitative research method which aims to explain a phenomenon by using numbers that describe the characteristics of the subject under study. The results of graph coloring made in this study produce at least 5 colors needed to color the map. The number of vertices (villages) on the Alor Island map is 120, and the chromatic number in the graph of the Village map on Alor Island is 5 (. The vertices (villages on Alor Island) can be colored using only five colors, and between Villages that border each other have different colors.